Examining Muslims’ Aspirations in Drafting the New Criminal Code: Analyzing Criminal Law Policy in Indonesia from a Maslaha Perspective - Ariyanti, Vivi; Supani (Al-Manahij: Jurnal Kajian Hukum Islam, 2024)
Indonesia is a Muslim-majority country that has enacted Law Number 1 of 2023 concerning the Criminal Code as a common ideal between the state and its citizens in creating harmony in life. In a democratic country, the law-making process must open to public participation as a form of manifestation of the determination of the society’s living values, and as providing legitimacy for the formation of a law. This study focuses on discussing how much the aspirations of Muslims are adopted by the state in drafting the new Criminal Code, especially on issues related to Islamic morality, such as pornography, displaying contraceptives, adultery, cohabitation, abortion, and blasphemy. This study uses qualitative research methods with maslaha theory approach. The data sources are in the form of laws and regulations, minutes of DPR sessions, and the aspirations of the Islamic community. This study concludes that the new Criminal Code shows an increase in meaningful participation, which includes three prerequisites: the public has the right to be heard, the right to have their opinions considered, and the right to receive an explanation. The drafting of the new Criminal Code is at the “partnership” level and is in the “degrees of citizen power” category in the ladder of citizen participation scheme. At this level, the public has direct access to interact with policy makers regarding the new Criminal Code.